Augmented Reality as an ICT Innovation to Enhance Digital Literacy and Mathematical Problem-Solving Ability: A Systematic Literature Review - Rikhel Saputri; Sugiman; Diah Dwi Santri (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2026)
The rapid advancement of Information and Communication Technology (ICT) has created unprecedented opportunities for innovation in mathematics education, particularly through the integration of Augmented Reality (AR). This study presents a Systematic Literature Review (SLR) examining the role of AR as an ICT-based innovation in developing students' digital literacy and mathematical problem-solving ability. Following the PRISMA 2020 protocol, a comprehensive search was conducted across five databases—Scopus, Web of Science, ERIC, Google Scholar, and Garuda—yielding 127 initially identified articles. After applying rigorous inclusion and exclusion criteria, 25 peer-reviewed articles published between 2020 and 2025 were selected for in-depth analysis. The findings reveal that: (1) AR consistently improves students' mathematical problem-solving ability, with average score gains ranging from 18% to 34% relative to conventional instruction; (2) AR meaningfully supports the development of digital literacy by engaging students in multimodal, technology-mediated learning experiences; (3) the effectiveness of AR is substantially moderated by the quality of pedagogical design, with inquiry-based, problem-based, and gamification frameworks yielding the strongest outcomes; and (4) key implementation barriers include device accessibility, teacher digital competence, and instructional time constraints. Critically, this review identifies a salient gap in the literature: very few studies have integrated AR with local cultural contexts in Indonesian mathematics classrooms, pointing toward a promising direction for developing contextually grounded and culturally responsive learning models.